2001
DOI: 10.1128/mcb.21.11.3704-3713.2001
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Transgenic Knockdown of Fos-Related Antigen 2 (Fra-2) Expression Mediated by Dominant Negative Fra-2

Abstract: Fos-related antigen 2 (Fra-2) is a member of the Fos family of immediate-early genes, most of which are rapidly induced by second messengers. All members of this family act by binding to AP-1 sites as heterodimeric complexes with other proteins. However, each appears to have a distinct role. The role and biology of Fra-2 are less well understood than those of its relatives c-Fos, Fra-1, and FosB; moreover, Fra-2 target genes remain largely unknown, as does the basis of its selective effects on transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 45 publications
4
54
0
Order By: Relevance
“…Fra2 was expected to be an inhibitory transcription factor involved in the decrease in Aa-nat mRNA in the morning MULTIPLE REGULATION OF PINEAL MELATONIN SYNTHESIS IN MAMMALS . However, this hypothesis is ruled out by the recent finding that pineal Aa-nat gene expression is not altered in transgenic rats with a dominant negative Fra2 gene (Smith et al, 2001). The daily AP-1 variation in the pineal gland is probably involved in some other transcriptional regulation.…”
Section: The Third Messengers/transcription Factorsmentioning
confidence: 66%
“…Fra2 was expected to be an inhibitory transcription factor involved in the decrease in Aa-nat mRNA in the morning MULTIPLE REGULATION OF PINEAL MELATONIN SYNTHESIS IN MAMMALS . However, this hypothesis is ruled out by the recent finding that pineal Aa-nat gene expression is not altered in transgenic rats with a dominant negative Fra2 gene (Smith et al, 2001). The daily AP-1 variation in the pineal gland is probably involved in some other transcriptional regulation.…”
Section: The Third Messengers/transcription Factorsmentioning
confidence: 66%
“…In earlier studies, calcium has been shown to be capable of inducing Fra-2 (Herdegen and Leah, 1998). Similar to other members of the fos family, Fra-2 is known to form heterodimeric complexes with other proteins, such as Jun and CREB family members (Herdegen and Leah, 1998;Smith et al, 2001). Moreover, Fra-2 can regulate the expression of other genes through interactions with the AP-1 DNA consensus element (Foletta, 1996;Boss et al, 2001).…”
mentioning
confidence: 99%
“…These findings led to the hypothesis that cocaine may exert effects on IEGs, such as fra-2, which in turn alter the regulation of target late genes, one of which may be the 1 receptor. Because Fra-2 can form heterodimers with other transcription factors and bind to activator protein 1 (AP-1) sites (Herdegen and Leah, 1998;Smith et al, 2001), the presence of an AP-1 binding site on the 1 receptor promoter (Seth et al, 1997) suggested a mechanism through which the gene could be transcriptionally regulated. Subsequent cocaine-induced increases in 1 receptor expression may then lead to altered behavioral responses to later cocaine challenges, which can be expressed as sensitization.…”
mentioning
confidence: 99%
“…In the pineal gland, cAMP treatment results in an elevation of c-Fos and Fos-related antigen-2, both of which bind to AP-1 sites. Either or both could mediate cAMP stimulation of MAT2A transcription (28,31).…”
Section: Discussionmentioning
confidence: 99%